SCHOOL STRATEGY IN IMPROVING STUDENT ENTREPRENEURSHIP SKILLS - Handayani, Arinda; Suranto, (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
This study aims to understand the efforts of SMK N 1 Karanganyar in fostering entrepreneurial skills in students. Entrepreneurial skills are an important aspect to learn at this time given the unstable unemployment rate in Indonesia and the limited job opportunities. This research uses a case study approach with qualitative methods. Data were collected through interviews with principals, teachers, and students involved in the entrepreneurship skills development programme at SMK N 1 Karanganyar. The results showed that the school has made various innovations in providing entrepreneurship programmes. However, there are shortcomings in the implementation of Loket Medio, where not all students get practical experience in application-based services. This condition has the potential to cause knowledge inequality among students. In addition, the school does not have an alternative programme to overcome this obstacle. These findings emphasise the importance of improvements in the entrepreneurship programme to produce graduates who excel in entrepreneurship and are able to contribute to addressing the unemployment problem in Indonesia.